Influence of solution-state aggregation on conjugated polymer crystallization in thin films and microwire crystals. (August 2021) - Zheng, Yu-Qing; Yao, Ze-Fan; Dou, Jin-Hu; Wang, Yilin; Ma, Wei; Zou, Lin; Nikzad, Shayla; Li, Qi-Yi; Sun, Ze-Hao; Yu, Zhi-Ao; Zhang, Wen-Bin; Wang, Jie-Yu; et al.
Abstract: Highly ordered nanostructures assembled from conjugated polymers have great potential for probing fundamental structure-property relationships, as well as boosting the charge transport performance. To date, the effect of solution-state aggregation on crystallization and charge transport in conjugated polymers is still unclear and in need of precise description at the molecular level. In this work, we report a systematic study of solution-state aggregation on crystallization and charge transport in BDOPV-based conjugated polymers through side chain engineering. Detailed analysis of crystal packing structures of conjugated polymers reveals that intermolecular displacements are substantially modified in order to minimize steric hindrance caused by the alkyl side chains. Moreover, subtle differences in side chain chemical structures play a vital role in regulating solution-state aggregation, and thus crystalline domain sizes in both microwires and thin films. Farther branched side chain leads to larger polymer aggregates in solution and therefore larger crystalline domains in solid films. Subsequently, an increase in electron mobility is obtained with the highest mobility values surpassing 10 cm 2 V −1 s −1 . This work unravels that the modification of the side chains is an efficient strategy for fine-tuning the interchain organization of conjugated polymers from solution to solid state. Graphical abstract: Image, graphical abstract